2000
DOI: 10.1002/(sici)1099-0488(20000601)38:11<1440::aid-polb40>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization of copolymers of ethylene and 1‐octadecene

Abstract: Four ethylene-1-octadecene copolymers and the corresponding polyethylene homopolymer, synthesized with a metallocene catalyst, have been analyzed by using three characterization techniques in the solid state: differential scanning calorimetry, wide-angle X-ray diffraction, and Raman spectroscopy. Very important annealing effects are observed in the copolymers with higher comonomer content while standing at room temperature, in such a way that the enthalpies of melting derived from the first and second melting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 0 publications
6
22
0
Order By: Relevance
“…This indicates fundamental differences in the crystalline structure. This structure was discussed by Pérez et al [43], who found very similar DSC-traces for their sample. Based on their results, they concluded that the octadecene sidechains do not crystallize themselves separately, which is in accordance with Piel et al [16], who didn't find side-chain crystallization by DMTA.…”
Section: Dscsupporting
confidence: 62%
See 1 more Smart Citation
“…This indicates fundamental differences in the crystalline structure. This structure was discussed by Pérez et al [43], who found very similar DSC-traces for their sample. Based on their results, they concluded that the octadecene sidechains do not crystallize themselves separately, which is in accordance with Piel et al [16], who didn't find side-chain crystallization by DMTA.…”
Section: Dscsupporting
confidence: 62%
“…The SEC-MALLS-data of both materials show no deviation from the linear reference within the accuracy of the experiment, which points to the fact that neither material contains any long-chain branching (see Ref. [43] for an in-depth discussion of the question of how long-chain branching can be detected in PE). Table 1 shows the molecular characteristics of the samples characterized.…”
Section: Rheologymentioning
confidence: 63%
“…The crystallinity from Raman spectra has been determined following two different protocols: the classical 14,15 and the new one 16,17 in which the band at 1065 cm −1 is considered with a normalization constant of 0.80. The difference between both of protocols comes from the interpretation of a third component within the structure.…”
Section: A Crystalline Structurementioning
confidence: 99%
“…The XRD patterns proposed by Perez et al [35] showed that there were two peaks at about 2y ¼ 19.8 and 21.48 for pure POE. The peak (2y ¼ 21.48) reflects the characteristics of the orthorhombic cell of polyethylene (PE) and the peak (2y ¼ 19.88) could be considered as indicatives of the side branches of octene in the crystalline structure.…”
Section: Xrdmentioning
confidence: 96%